Lithiation Mechanism Change Driven by Thermally Induced Grain Fining and Its Impact on the Performance of LiMn2O4 in Lithium‐Ion Batteries. Issue 29 (18th June 2020) - Lee, Geun Jun; Abbas, Muhammad A.; Lee, Moo Dong; Lee, Jeongmin; Lee, Junghyun; Bang, Jin Ho
Abstract: The nature of precursors employed in the synthesis of lithium‐ion battery cathode materials is a crucial performance‐dictating factor. Therefore, it is of great importance to establish a way to manipulate the precursor and seek a comprehensive understanding of its influence on the electrochemical behavior of a targeted electrode material. A thermal route is herein demonstrated for the synthesis of lithium‐excess LiMn2 O4 (LMO) by exploiting an intriguing thermal phenomenon, thermally induced grain fining, and sheds light on how it affects the mechanism and kinetics of lithiation, and, furthermore, the electrochemical behavior of LMO. Detailed insights into the lithiation mechanism and kinetics reveal that the use of a finely grained, porous Mn3 O4, which possesses an open crystal structure, is a key to the success of incorporating excess Li. In addition, this in‐depth electrochemical investigation verifies a very recent theoretical prediction of faster Li diffusion kinetics enabled by excess Li. Abstract : A new thermal route to the synthesis of LiMn2 O4 based on a thermally induced grain fining phenomenon is devised. The fundamental reaction mechanism of the synthesis is explored, and the important kinetic parameters are determined. In‐depth electrochemical investigation combined with the mechanism study verifies a very recent theoretical prediction on a faster Li diffusion kinetics enabled by excess Li.